Use a native XML database for your XML data deciding when an XQuery based native XML database is better than an SQL database. - Burd, Gregory
Developers tend to use the most familiar technologies. For data storage, that is the relational database. During design it's easy to see tables of data everywhere; however, not everything is relational in nature. When dealing with XML data or data easily expressed as XML, XQuery-based native XML databases (NXDs) present a viable and cost-effective alternative to relational databases, file system storage or custom developed storage implementations. So, when is it time to consider an NXD?